Hydroxyl vacancies triggered high methanol oxidation activity of monolayered layered double hydroxides for energy-saving hydrogen production. (August 2022) - Liu, Bin; Wang, Xiao; Wang, Suwen; Peng, Hui-Qing; Xiao, Tongyao; Liu, Guihao; Bai, Sha; Zhao, Yufei; Zhang, Wenjun; Song, Yu-Fei
Abstract: Monolayered Ni-based layered double hydroxides (LDHs) enriched with hydroxyl vacancies are synthesized and first applied in the methanol-assisted energy-saving hydrogen production system including independent electrolysis and photovoltaic-electrolysis. The rich hydroxyl vacancies are revealed to endow monolayered LDHs with significantly superior performance in the aspects of the activity for methanol oxidation reaction and the boosting effect for cathodic hydrogen production compared to the bulk counterparts. The theoretical and experimental results confirm that the hydroxyl vacancies can increase density of states near Fermi level of LDH (i.e. elevate electrical conductivity to form favorable charge transportation during electrocatalysis), and promote its adsorption and further cleavage for methanol, thus leading to the enhanced methanol oxidation reaction performance. Graphical abstract: Image 1 Highlights: Monolayered Ni-based LDHs with OH vacancies are applied in the methanol-assisted energy-saving hydrogen production. Rich OH vacancies are revealed to endow monolayered LDHs with superior performance. Enhancement mechanism associated with the OH vacancies existing in monolayered LDH is uncovered theoretically.